2012
DOI: 10.1007/s00210-012-0749-8
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone improves aging-related endothelial dysfunction in the rat mesenteric artery

Abstract: Aging-related endothelial dysfunction is characterized by blunted nitric oxide (NO)- and endothelium-derived hyperpolarizing factor (EDHF)-mediated relaxations in arteries, which may be due, at least in part, to increased oxidative stress. Endothelial dysfunction will promote the initiation and development of major cardiovascular diseases such as atherosclerosis and hypertension. Thymoquinone (TQ) is the most active constituent of the volatile oil of Nigella sativa seeds with well-documented antioxidative prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 65 publications
0
35
0
Order By: Relevance
“…106 A recent study showed that TQ improves aging-related endothelial dysfunction in the rat mesenteric artery. 107 The study was carried out on 12 middle-aged (46 weeks) male Wistar rats divided into 2 groups of 6 rats receiving either solvent (3% ethanol vol/vol) or TQ (10 mg/kg per day) in the drinking water for 14 days. Six male Wistar rats (16 weeks old) were used as young controls.…”
Section: Concord Grapesmentioning
confidence: 99%
See 3 more Smart Citations
“…106 A recent study showed that TQ improves aging-related endothelial dysfunction in the rat mesenteric artery. 107 The study was carried out on 12 middle-aged (46 weeks) male Wistar rats divided into 2 groups of 6 rats receiving either solvent (3% ethanol vol/vol) or TQ (10 mg/kg per day) in the drinking water for 14 days. Six male Wistar rats (16 weeks old) were used as young controls.…”
Section: Concord Grapesmentioning
confidence: 99%
“…Overall, these research findings specify that TQ improved aging-related endothelial dysfunction most likely by preventing oxidative stress and normalizing the angiotensin system. 107 Hawthorn extract (Crataegus ssp.) is a rich source of polyphenols, including a mixture of monomeric flavonoids and oligomeric procyanidins (OPCs).…”
Section: Concord Grapesmentioning
confidence: 99%
See 2 more Smart Citations
“…In mice, it protects against sepsis-induced morbidity and mortality (Alkharfy et al, 2011), and in rats, its chronic administration improves age-related endothelial dysfunction (Idris-Khodja and Schini-Kerth, 2012). In preliminary experiments on isolated rat arteries, aimed at investigating the vasodilator properties of thymoquinone, a serendipitous finding was that the compound actually augmented sustained contractions in preparations with endothelium ( Fig.…”
Section: Introductionmentioning
confidence: 99%